RETRACTED: FNDC1 Promotes the Invasiveness of Gastric Cancer via Wnt/β-Catenin Signaling Pathway and Correlates With Peritoneal Metastasis and Prognosis - Jiang, Tao; Gao, Wenyu; Lin, Shengjie; Chen, Hao; Du, Bin; Liu, Qing; Lin, Xiaoyan; Chen, Qiang (Frontiers in Oncology, 2020)
Background: Gastric cancer (GC) has a high morbidity and mortality rate, with peritoneal metastasis (PM) identified as the main site of metastasis. Our previous study found that FNDC1 has a higher frequency of mutations in patients with PM by high-throughput sequencing assay, suggesting that it may be associated with GC invasion and PM, however the specific mechanism remains unclear. Methods: First, the correlation between FNDC1 and PM and prognosis of GC was clarified by bioinformatics and clinicopathological analysis. Next, the effect of FNDC1 expression on the invasion and metastasis ability of GC was investigated in vivo and in vitro. Finally, the signaling pathways involved in the regulation of FNDC1 were explored. Results: FNDC1 was highly expressed in GC and was associated with PM and poor prognosis. FNDC1 was also associated with epithelial-mesenchymal transition (EMT) in GC cells. Through in vivo and in vitro experiments, it was clarified that knockdown of FNDC1 could inhibit the proliferation, invasion and migration of GC cells. In addition, it was elucidated that FNDC1 promotes EMT through the Wnt/β-catenin signaling pathway. Conclusion: FNDC1 may be associated with the invasion of GC and PM after surgery. FNDC1 was highly expressed in GC tissues and cell lines, while significantly associated with poor DFS and OS in GC patients. Both univariate and multivariate analyses suggested that the expression of FNDC1 was an independent factor for GC. Knockdown of FNDC1 also significantly inhibited the proliferation, migration and activity of GC cells. FNDC1 may promote EMT in GC cells through the regulation of Wnt/β-catenin signaling pathway. FNDC1 has the potential to be used as a predictor of PM and may also be studied in depth as a therapeutic target for GC, which has potential clinical utility and is worthy of further validation.